Self-Compassion As Moderator of Istiqomah Learning and Perfectionism in High School Students - Fauzyyah, Adhitia Wardani; Hawadi, Lydia Freyani; Hannase, Mulawarman (Journal Of Middle East and Islamic Studies, 2023)
Abstract The stages of adolescent development are generally at the age of high school students who are equipped with developmental tasks to have a good self-identity. Previous research mentioned that there was a public opinion that one form of achieving successful students' self-identity is that they succeed in becoming students at the State Higher Education Universities (PTN). In order to meet these perfect expectations, some students try to be istiqomah in learning by following tutoring program outside of school. By using quantitative research and data collection using purposive random sampling, this research tries to see how the relationship between istiqomah learning and perfectionism of high school students participating in tutoring and trying to see the effect of self-compassion as a moderator variable. Data obtained from 90 respondents showed that there is a significant relationship between Istiqomah learning and student perfectionism (r = 0.417, p = 0.00), there is a negative relationship between perfectionism and self-compassion (r = -0.329, p = 0.002), while self-compassion as a moderator has no significant effect on the relationship between the other two variables (Int_1 t= -0.3052, p = 0.7609).